The role of IL-36γ and its regulation in eosinophilic inflammation in allergic rhinitis. (May 2019) - Qin, Xiaowei; Liu, Mengting; Zhang, Shuoying; Wang, Chunrui; Zhang, Tianhong
Highlights: The expression of IL-36γ and its receptor IL-36R by eosinophils in AR were up-regulated. IL-36γ exaggerates eosinophilic inflammation in AR by promoting the function of eosinophils. Human nasal epithelial cells secrete IL-36γ after treated with recombinant IL-17, IL-25, IL-33. Abstract: Background: Allergic rhinitis (AR) is characterized by eosinophilic inflammation. However, the function and regulation of eosinophils in AR are largely unknown. This study aimed to explore the expression and role of interleukin-36 (IL-36) cytokines in AR. Methods: Sixty AR patients and 20 control subjects were recruited in this study. The mRNA and protein expression of serum IL-36 family cytokines and IL-36R in AR were detected by quantitative RT-PCR and enzyme-linked immunosorbent assay ELISA, respectively. IL-36R expression and regulation by eosinophils and the role of IL-36γ in the survival, adhesion, migration and activation of eosinophils were performed in purified eosinophils. Human nasal epithelial cell line was cultured and treated with different stimulators and IL-36γ was measured. Results: The mRNA and protein expression of serum IL-36 cytokines and IL-36R were significantly higher in AR compared with control, especially in asthmatic patients. Among the IL-36 cytokines, the expression of IL-36γ was the highest. The expression of IL-36R by eosinophils were significantly increased compared with normal controls and was up-regulated by recombinant IL-17, IL-25, IL-33 and Dermatophagoides pteronyssinus group 1. The IL-36γ promote the survival, adhesion, migration and activation of eosinophils. Human nasal epithelial cells can secrete IL-36γ after treated with recombinant IL-17, IL-25, IL-33. Conclusions: High expression of IL-36γ exaggerates eosinophilic inflammation in AR by promoting the survival, adhesion, and activation of eosinophils.